Ensuring Information Security Is A Factor In Ensuring The Stability Of Society (Open Herald: Periodical of Methodical Research, 2023)
The article analyzes the processes of emergence of information security problems along with the globalization of information and communication technologies. In addition, the main focus of the article is on cyber attacks, the growth of cybercrime, the measures taken by the government of Uzbekistan against it, and the processes of combating this "plague" of the 21st century.